Usefulness of Daniels’ biopsy in lung cancer staging - Kamiński, Janusz; Kozielski, Jerzy; Dzielicki, Józef; Czyżewski, Damian (Contemporary Oncology/Współczesna Onkologia, 2004)
Aim of the study. To assess the value of histological examination of supraclavicular and scalene lymph nodes in lung cancer staging. Material and Methods. This is a retrospective analysis of 56 patients with neoplasms presented in the study. The patients were hospitalised at the Department of Lung Diseases and Tuberculosis in 1997-2001. The presence of metastases in the examined nodes was evaluated in correlation with the physical examination, the type of neoplasm and the presence of nodular lesions in mediastinum in computed tomography (CT) presentation. Results. The results of Daniels’ biopsy were positive in 13 patients among the analyzed 56 patients (23%). The presence of enlarged lymph nodes in mediastinum in CT presentation of the chest was found in all the patients of this group. Lymph nodes were palpable in 6 among 13 patients with a positive result of Daniels’ biopsy (46%). Enlarged lymph nodes in CT presentation of the chest were found in 20 patients in a group of 43 patients with a negative result of Daniels’ biopsy (47%). Lymph nodes were not palpable in 7 patients among 13 patients with a positive result of Daniels’ biopsy. In the case of 10 patients, although lymph nodes were palpable, the presence of neoplasmatic lesions in their histological examination was not confirmed. Conclusions. Palpation of the supraclavicular and scalene lymph nodes does not correlate with the presence of metastases. If the result of histological examination of supraclavicular or scalene lymph nodes is positive, it may suggest the presence of metastases within the lymph nodes in mediastinum.